MRI of the brainstem in patients with major depression, bipolar affective disorder and normal controls. - Supprian, T; Reiche, W; Schmitz, B; Grunwald, I; Backens, M; Hofmann, E; Georg, T; Falkai, P; Reith, W (2004)
Structural imaging studies of bipolar affective disorder or major depression have shown a spectrum of abnormal findings. However, a characteristic pattern of abnormality for either disease has not yet emerged. While the majority of studies focused on brain atrophy and the volumes of supratentorial cerebral structures, little attention has been paid to infratentorial structures. This MRI study focused on the pontomesencephalic area including the region of the raphe nuclei. The raphe nuclei are of special interest in affective disorders as they are the origin of the major serotonergic projections in this region. MRI scans of 10 bipolar I patients, 10 patients with major depression and 10 age-matched healthy control subjects were studied. The brain stem and the fourth ventricle areas as well as T2-relaxation times in the area of the raphe nuclei were evaluated. A difference between patients with major depression and control subjects for T(2)-relaxation times was found in a region of interest located along the midline of the pons. No difference was found between patients with bipolar disorder and control subjects. This finding needs to be replicated in a larger sample with more elaborated MRI techniques (multi-echo sequences) for the determination of T2-relaxation times.